2017
DOI: 10.1371/journal.pntd.0006027
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of life-threatening invasive nontyphoidal Salmonella disease in Malawian children: A prospective observational study

Abstract: Nontyphoidal Salmonellae commonly cause invasive disease in African children that is often fatal. The clinical diagnosis of these infections is hampered by the absence of a clear clinical syndrome. Drug resistance means that empirical antibiotic therapy is often ineffective and currently no vaccine is available. The study objective was to identify risk factors for mortality among children presenting to hospital with invasive Salmonella disease in Africa. We conducted a prospective study enrolling consecutive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 52 publications
(90 reference statements)
1
18
0
Order By: Relevance
“…However, we did not find a significant difference in the morbidity of respiratory tract infection between iNTS cases and NTS cases. Previous studies have revealed that the risk factors for invasive disease in children included young age and immunosuppression of any cause [7,39,40], which were also revealed in the present study, as infants aged �6 months and children with the underlying medical condition of leukemia were prone to have iNTS infection.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 81%
See 1 more Smart Citation
“…However, we did not find a significant difference in the morbidity of respiratory tract infection between iNTS cases and NTS cases. Previous studies have revealed that the risk factors for invasive disease in children included young age and immunosuppression of any cause [7,39,40], which were also revealed in the present study, as infants aged �6 months and children with the underlying medical condition of leukemia were prone to have iNTS infection.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 81%
“…It was confirmed in our study with the incidence of diarrhea being significantly higher in the non-iNTS infection cases. In addition, some studies have reported that symptoms of pneumonia and respiratory distress occurred frequently in children with iNTS [9,38,39]. https://doi.org/10.1371/journal.pntd.0008732.g004…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Over the years in DRC, MDR remained widespread in all serotypes, whereas recent data from Mali [47], Malawi [45,60], South-Africa [61], Kenya [62][63][64] and Ghana [65] showed MDR to be less frequent in Salmonella Enteritidis or more variable over time. Since 2013, resistance to ceftriaxone and azithromycin and DCS increased substantially in O5-positive Salmonella Typhimurium in DRC.…”
Section: Comparison With Other Sub-saharan African Countriesmentioning
confidence: 95%
“…The effectiveness of antibiotic treatment is hampered by the difficulty in making a diagnosis, the sudden onset of the disease, and the growing frequency of multidrug resistance ( 1 , 2 , 5 ). Higher incidence and increased severity of iNTS disease have been observed in young children below 72 mo of age, in patients with malaria, anemia, malnutrition, HIV, sickle cell disease, and hemolysis ( 6 9 ). Moreover, the Global Burden of Disease Study 2015 estimated that NTS is the third commonest cause of diarrheal deaths at 90,300 (95% uncertainty interval, 34,100–183,100) ( 10 ).…”
mentioning
confidence: 99%